Estudio de aplicabilidad de material biocompuesto con fibra de cascarilla de arroz para la fabricación de engranajes de diente recto para aplicaciones de baja carga - Galeano Medina, Jossi Esteban (Universidad Antonio Nariño, 2021)
The project is based on studying the application of biocomposite material with rice husk (CA) for the manufacture of flat tooth gears for low power transmission systems; This idea arises from the need to find different alternatives to the metal and plastic gears used in the industry. Power transmission systems are designed mainly with flat tooth metal gears, characterized by being heavy, expensive to manufacture, difficult to machine, very noisy and require constant lubrication, therefore it is necessary to study design alternatives for these mechanical systems.